Adverse reactions to medication on a coronary care unit. Issue 650 (December 1979) - Falk, Rodney H.
Abstract : In a prospective survey of treatment on a coronary care unit 23·6% of patients who received medication had one or more side effects. In several cases these were severe enough to cause marked deterioration of the patient's clinical status. Whilst antiarrhythmic therapy is an integral part of modern coronary care its potential hazards should be recognized, particularly in the elderly patient.